2020
DOI: 10.1186/s12978-020-01005-7
|View full text |Cite
|
Sign up to set email alerts
|

An overview of the sexual and reproductive health status and service delivery among Syrian refugees in Jordan, nine years since the crisis: a systematic literature review

Abstract: Background The Syrian refugee crisis has led to massive displacement into neighboring countries including Jordan. This crisis has caused a significant strain on the sexual and reproductive health (SRH) services to the host communities and Syrian refugees. The Minimum Initial Service Package (MISP) is a standard package of services that should be implemented at the onset of an emergency. Due to their importance in protracted humanitarian crisis, this systematic review aimed to assess the utiliza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 18 publications
0
19
0
Order By: Relevance
“…Mistreatment by staff, high cost, poor quality of services, long waiting times, far distances, and unaffordable means of transport were the obstacles mentioned by participants. Comparable barriers are observed in Syrian refugee populations in Jordan and Turkey [ 51 , 52 ], in addition to other displaced populations such as refugee adolescent girls in the Nakivale refugee settlement in Uganda [ 44 ]. Surprisingly, and in contrary to other studies on Syrian refugee women in Jordan and Turkey [ 35 , 53 , 54 ], the sex of the healthcare provider was not named as a barrier to SRH services access.…”
Section: Discussionmentioning
confidence: 99%
“…Mistreatment by staff, high cost, poor quality of services, long waiting times, far distances, and unaffordable means of transport were the obstacles mentioned by participants. Comparable barriers are observed in Syrian refugee populations in Jordan and Turkey [ 51 , 52 ], in addition to other displaced populations such as refugee adolescent girls in the Nakivale refugee settlement in Uganda [ 44 ]. Surprisingly, and in contrary to other studies on Syrian refugee women in Jordan and Turkey [ 35 , 53 , 54 ], the sex of the healthcare provider was not named as a barrier to SRH services access.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, most women in high-income countries have free or low cost universal SRH access in primary health care including screening for reproductive cancers [ 24 ]. The poor quality of SRH care but also a lack of available services, leads to low utilisation of these services [ 25 ] further contributing to barriers refugee and displaced women may experience in accessing care [ 26 ]. In 2004, a global evaluation of reproductive health services for refugees and internally displaced people concluded that most people affected by conflict lack adequate SRH care.…”
Section: Introductionmentioning
confidence: 99%
“…More than a million Syrians are estimated as being displaced in Jordan on account of the war that began in 2011, with the vast majority of the more than 600,000 refugees registered with UNHCR living outside of camp settings [ 38 ]. A recent systematic review found that while the exact prevalence of sexual violence among displaced Syrian women is unclear, they are at risk for multiple forms of violence including early and/or forced marriage, and approximately one third of Syrian refugees surveyed in Lebanon reported exposure to conflict-related violence [ 39 , 40 ]. Since the early 1990s when the Dadaab camp was established, Somali refugees have fled to Kenya on account of civil war, drought, and famine [ 41 ].…”
Section: Methodsmentioning
confidence: 99%